Umbilical scar autonomization: a safe technique for secondary abdominoplasties Autonomização da cicatriz umbilical: técnica segura para abdominoplastias secundárias - Liacyr Ribeiro; Marcelo Castro Marcal Pessoa; Roberto Braga Rocha (Revista Brasileira de Cirurgia Plástica, 2011)
BACKGROUND: In lipominiabdominoplasty and mid-abdominoplasty procedures, the umbilicus is usually undermined from its aponeurotic fixation; this modifies its normal vascular pattern. In patients undergoing these procedures and candidates for a secondary classic abdominoplasty, trophic changes, including necrosis, may occur in the umbilical scar. To avoid trophic complications in the neo-umbilicus, autonomization of the umbilical scar was carried out. METHODS: Three candidates for a secondary classic abdominoplasty underwent the umbilicus autonomization process in the private clinic of the corresponding author. One incision, 1 cm from the umbilical scar, was performed from the skin to the aponeurotic plane on each side, with an interval of 15 days between the two surgical incisions. After the second incision, the patient waited for a further 15 days. Thus, the whole process took 30 days before classic abdominoplasty was performed. RESULTS: No trophic alterations or necrosis in the umbilical scar were observed in these cases. CONCLUSIONS: The aesthetic results were satisfactory, indicating the effectiveness of this method INTRODUÇÃO: Nos procedimentos de lipominiabdominoplastia e midiabdominoplastia, usualmente, o umbigo é destacado de sua fixação aponeurótica, o que modifica o padrão vascular do umbigo. Em pacientes submetidos a esses procedimentos e candidatos a abdominoplastia clássica secundária, podem ocorrer alterações tróficas da cicatriz umbilical e, até mesmo, necroses. Utilizou-se a manobra de autonomização da cicatriz umbilical para evitar complicações tróficas do neoumbigo. MÉTODO: Foram submetidas ao processo de autonomização da cicatriz umbilical 3 pacientes candidatas a abdominoplastia clássica secundária, na clínica privada do autor principal. A técnica compreende uma incisão a 1 cm da cicatriz umbilical, desde a pele até o plano aponeurótico, de cada lado, com intervalo de 15 dias entre cada etapa, no total de dois tempos cirúrgicos. O processo como um todo leva 30 dias, antes da abdominoplastia clássica. RESULTADOS: Não foram observadas alterações tróficas ou necroses da cicatriz umbilical nos casos submetidos ao processo de autonomização. CONCLUSÕES: Os resultados estéticos foram satisfatórios, o que atestou a efetividade do método